2017
DOI: 10.1038/ja.2017.145
|View full text |Cite|
|
Sign up to set email alerts
|

Halistanol sulfates I and J, new SIRT1–3 inhibitory steroid sulfates from a marine sponge of the genus Halichondria

Abstract: Two new analogs of halistanol sulfate (1) were isolated from a marine sponge Halichondria sp. collected at Hachijo-jima Island. Structures of these new halistanol sulfates I (2) and J (3) were elucidated by spectral analyses. Compounds 1-3 showed inhibitory activity against SIRT 1-3 with IC ranges of 45.9-67.9, 18.9-21.1 and 21.8-37.5 μM, respectively. X-ray crystallography of the halistanol sulfate (1) and SIRT3 complex clearly indicates that 1 binds to the exosite of SIRT3 that we have discovered in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Detailed analysis of the 1 H and 13 C NMR, COSY, HSQC, HMBC, and NOESY spectra of 10 (CD 3 OD, Table 1 and Table 2, Figure 2, substructures II and VIII, Figures S39–S44) and a comparison of its 1 H and 13 C chemical shift values with those reported in the literature for the previously described trisulfated steroids [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18], indicated that 10 is a previously unreported 4 β -hydroxy derivative of halistanol sulfate C [3], which was named 4 β -hydroxyhalistanol sulfate C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed analysis of the 1 H and 13 C NMR, COSY, HSQC, HMBC, and NOESY spectra of 10 (CD 3 OD, Table 1 and Table 2, Figure 2, substructures II and VIII, Figures S39–S44) and a comparison of its 1 H and 13 C chemical shift values with those reported in the literature for the previously described trisulfated steroids [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18], indicated that 10 is a previously unreported 4 β -hydroxy derivative of halistanol sulfate C [3], which was named 4 β -hydroxyhalistanol sulfate C.…”
Section: Resultsmentioning
confidence: 99%
“…[3,4], Pseudoaxinissa digitata [5], and Halichondria sp. [6], ophirapsranol trisulfate from Topsentia ophiraphidites [7], four sterols isolated from the sponges Trachyopsis halichondroides and Cymbastela coralliophila [8], amaranzoles A-F from Phorbas amaranthus [9,10], and topsentinol K trisulfate from the sponge Topsentia sp. [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New analogues of the known trisulfate compound halistanol sulfate 155 bearing cyclopropyl rings on their side chains have been isolated from the marine sponge Halichondria sp. Halistanol sulfates I 156 and J 157 had IC 50 values for sirtuins 1–3 of 45.9, 18.9, and 32.6 µM and 67.9, 21.1, and 37.5 µM, respectively, compared to IC 50 s of the parent structure 105 of 49.1, 19.2, and 21.8 µM [ 103 ].…”
Section: Bioactive Steroidal Metabolitesmentioning
confidence: 99%
“…Marine invertebrates are immensely diverse, well distributed in the world oceans [8], and widely known to contain medicinally relevant molecules [9,10,11]. While these metabolites play different roles in nature, e.g., they act as chemical defense, chemical communication or reproductive signaling molecules, they also find application as human medicines [12].…”
Section: Introductionmentioning
confidence: 99%